Production of hydrogen by borohydride: in search of low cost non-noble efficient catalyst - Rangel, C. M. (2009)
Hydrogen production by sodium borohydride through hydrolysis in alkaline solutions has been extensively studied as a production/storage option due to the high volumetric and gravimetric efficiency exhibited. The potential application of this option is based on an easily controllable catalysed hydrolysis reaction, non-toxic and recyclable by-products, and the high purity hydrogen produced can be used in fuel cells. This work reports on a comparative study of own-developed, supported and non-supported, nonnoble catalyst. Ru based catalysts are taken as reference. Characterization of the catalyst was accomplished using a FEG-SEM scanning electron microscope and FTIR analysis. Obtained values amount to 10 NLmin-1g-1 for Ni-based catalyst while Ru-based catalyst amount to twice as much in the same experimental conditions. Typical solutions contain sodium borohydride of concentrations between 2 and 10 wt%, stabilized with 3 to 10 wt % NaOH. Produced hydrogen is measured at ambient pressure as a function of catalyst exposure time at controlled temperatures till completion of the reaction. A thorough study of the open literature rendered normalized values for the reaction rate with different catalyst, making comparisons valuable.